1995
DOI: 10.1111/j.2044-8325.1995.tb00578.x
|View full text |Cite
|
Sign up to set email alerts
|

Police stress and well‐being: Integrating personality, coping and daily work experiences

Abstract: What are the personal and work related factors which contribute to a police officer's psychological well-being? This question was examined within a Perceived Quality of Life (PQOL) framework that integrates personality, coping processes and a police officer's positive (beneficial to well-being) and negative (harmful to well-being) work experiences. Structural equation analyses were conducted on questionnaire data obtained from 527 police officers during two related studies. Two structural equation models showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
201
3
3

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 229 publications
(222 citation statements)
references
References 30 publications
15
201
3
3
Order By: Relevance
“…In the study carried out by Hart, Wearing, and Headey (1995) upon investigating the effect of police officers' daily work experiences and personality traits upon their stress and well-being levels, they determined that both negative work experiences and positive work experiences negatively affected their perceived life quality. ies.ccsenet.org International Education Studies Vol.…”
Section: Introductionmentioning
confidence: 99%
“…In the study carried out by Hart, Wearing, and Headey (1995) upon investigating the effect of police officers' daily work experiences and personality traits upon their stress and well-being levels, they determined that both negative work experiences and positive work experiences negatively affected their perceived life quality. ies.ccsenet.org International Education Studies Vol.…”
Section: Introductionmentioning
confidence: 99%
“…And regarding the objectives of the coping strategies, it can be oriented towards the problem or oriented to the emotion (Lazarus & Folkman, 1986;Edwards, 1988;Begley, 1998). It seems that the coping strategies that oriented to the problem exert more benefits than strategies oriented to the emotion or avoidance (Roger, Jarvis & Najarian, 1993;Hart et al, 1995), and it would be more effective when the potential stresses of the environment are well controlled (Folkman, 1984;Edwards, 1988;Dewe, 1987;Labrador, 1995;Peiró& Salvador, 1993;Long, 1998;Ito & Brotheridge, 200;Peñacoba, et al, 2000). Thornton (1992) found that there is an association between avoidance as coping strategies and burnout.…”
Section: Coping Strategymentioning
confidence: 99%
“…Stress as a response strategy is rooted in the biological work of Selye (1976). He argued that stress is the psychological response to stressors involving all body organs which in the long term weakens the body's defence system and is reflected in the subject's emotional responses, e.g., anxiety, anger, irritation, depression and inability to concentrate (Hart & Cotton, 2003;Hart, Wearing, & Headey, 1995;Selye, 1976). Selye differentiated between distress (negative stress) which is associated with negative feelings and eustress (positive stress) associated with positive feelings that motivate individuals towards their higher achievements (Coon & Mitterer, 2008;Selye, 1976).…”
Section: Propositionmentioning
confidence: 99%